Estetizar el exceso: Cleopatra en la cultura hispánica medieval y del Siglo de Oro - Belmonte, Javier Jiménez (Boydell and Brewer : Boydell & Brewer, 2018)
Aestheticizing Excess: Cleopatra in Medieval Hispanic Culture and the Golden Age I/I is the first academic monograph to deal, in a comprehensive and systematic manner, with the cultural representations of Cleopatra produced in Spain from the 13th to 17th centuries. This study aims, on the one hand, to add an important chapter, although neglected by critics, to the complex cultural history of that icon. On the other hand, it proposes to use the different appropriations that medieval and aurisecular Spanish ideologues, intellectuals and artists carried out of that icon to investigate various socio-cultural processes that were taking place at that time, in particular, in the process of aestheticization that accompanied the development of a new court society from the end of the Middle Ages. Throughout five chapters--each not focused on a specific literary genre or artistic form, from historiography to poetry, theater, painting or tapestry--and adopting an interdisciplinary perspective, Aestheticizing excess puts the cleopatric icon with some of the main cultural, social and political debates of medieval and imperial Spain, using it as a starting point to reflect, among other things, on the way in which history was understood and written, questioned gender relations and redefined, the Other, domestic and foreign, represented and consumed, the senses exploited and controlled, or the way in which literature and art became part of the new strategies of social distinction and political positioning. Javier Jiménez Belmonte is Professor of Spanish Literature at Fordham University.